Phylogenetic diversity of methanogenic archae in diets with different hay proportions Diversidade filogenética de archaea metanogênica em dietas com diferentes proporções de feno - Marta de Campos Neves; Luciano Takeshi Kishi; Eliane Cristina da Cunha Alves; Jane Maria Bertocco Ezequiel; Manoel Victor Franco Lemos (Revista de Ciências Agrárias, 2010)
The objective of this research was to detect the presence of archaea in the bovine rumen using genetic sequences from the conserved region of the 16S rDNA. Samples were collected from bovines that were fed two different experimental dietetic ratios of roughage to concentrate. The 16S rDNA region was amplified using PCR and analyzed using the Phred/Phrap/Consed programs. For the treatment with 70% hay diet 96 sequences related to the Methanobacteriaceae family, 47 sequences from non-cultured archaea, and 60 sequences from unknown archaea were identified by the BLAST analysis. For the treatment with 30% hay diet the BLAST analysis identified 125 sequences belonging to the Methanobacteriaceae fa-mily 42 sequences from non-cultured archaea, and 32 sequences from unknown archaea. The analysis of the 16S rDNA sequences of archaea collected from the bovine rumen, allows more sequences matching the unknown archaea were identified in the treatment with 70% hay. O objetivo deste trabalho foi detectar a presença de arqueias no rúmen bovino por meio das sequências gênicas da região conservada 16S rDNA. As amostras foram coletadas de bovinos alimentados com duas dietas experimentais contendo diferentes relações volumoso e concentrado. Para amplificação da região ribossomal 16S rDNA foi feita PCR e a análise das sequências foi realizada pelos programas Phred/Phrap/Consed. As análises do BLAST permitiram identificar no tratamento com 70% de feno, 96 sequências relacionadas à família Methanobacteriaceae, 47 sequências a arqueias não cultiváveis e 60 sequências foram de arqueias desconhecidas e no tratamento com 30% de feno foram 125 sequências relacionadas à família Methanobacteriaceae, 42 sequências a arqueias não cultiváveis e 32 sequências foram de arqueias desconhecidas. A análise das sequências da região 16S rDNA de arqueias do rúmen bovino permitiu detectar maior número de sequências relacionadas com arqueias desconhecidas no tratamento com 70% de feno.